‘The Muncy–Vitell Consumer Ethics Scale: A Modification and Application’ - Vitell, Scott J. (Journal of business ethics, 2005)
This study compares college students with other adults in terms of the Muncy–Vitell (1992) consumer ethics scale. Further, the study updates the Muncy–Vitell consumer ethics scale with modifications that include rewording and the addition of new items. These new items can be grouped into three distinct categories – (1) downloading/buying counterfeit goods, (2) recycling/environmental awareness and (3) doing the right thing/doing good. The study also compares these two groups in terms of their attitude toward business. Results show that there is indeed a significant difference between these two groups in terms of ethical perceptions, but not in terms of the “recycling” items and the “doing good” items. There was also little difference between the groups in terms of their attitude toward business indicating that attitude toward business does not explain their different ethical perspectives.